Early treatment of patient with Class III skeletal and dental patterns - Bittencourt,Marcos Alan Vieira (2015)
Abstract Class III skeletal pattern is characterized by disharmony between maxillary and mandibular basal bones anteroposteriorly, and might or might not be associated with dental changes. In general, facial esthetics is hindered significantly, which most of times is the reason why patients or patient's guardians seek treatment. This case was presented to the Brazilian Board of Orthodontics and Dentofacial Orthopedics (BBO) in partial fulfillment of the requirements for Diplomate recertification and revalidation.